Losing the ability in activities of daily living in the oldest old: a hierarchic disability scale from the Newcastle 85+ study. - Andrew Kingston; Joanna Collerton; Karen Davies; John Bond; Louise Robinson; Carol Jagger (PLoS ONE)
Objectives To investigate the order in which 85 year olds develop difficulty in performing a wide range of daily activities covering basic personal care, household care and mobility. Design Cross-sectional analysis of baseline data from a cohort study. Setting Newcastle upon Tyne and North Tyneside, UK. Participants Individuals born in 1921, registered with participating general practices. Measurements Detailed health assessment including 17 activities of daily living related to basic personal care, household care and mobility. Questions were of the form 'Can you …' rather than 'Do you…' Principal Component Analysis (PCA) was used to confirm a single underlying dimension for the items and Mokken Scaling was used to determine a subsequent hierarchy. Validity of the hierarchical scale was assessed by its associations with known predictors of disability. Results 839 people within the Newcastle 85+ study for whom complete information was available on self-reported Activities of Daily Living (ADL). PCA confirmed a single underlying dimension; Mokken scaling confirmed a hierarchic scale where 'Cutting toenails' was the first item with which participants had difficulty and 'feeding' the last. The ordering of loss differed between men and women. Difficulty with 'shopping' and 'heavy housework' were reported earlier by women whilst men reported 'walking 400 yards' earlier. Items formed clusters corresponding to strength, balance, lower and upper body involvement and domains specifically required for balance and upper/lower limb functional integrity. Conclusion This comprehensive investigation of ordering of ability in activities in 85 year olds will inform researchers and practitioners assessing older people for onset of disability and subsequent care needs.